2004
DOI: 10.1557/proc-834-j6.1
|View full text |Cite
|
Sign up to set email alerts
|

Application of Magnetic Garnet Films for Magnetooptical Imaging of Magnetic Field Distributions

Abstract: Rare-earth iron garnet films of high quality can be grown by liquid phase epitaxy on paramagnetic substrates of gadolinium galliumgarnet. Such films are currently used for imaging of the spatial distribution of magnetic fields. This application is based on the Faraday rotation which can strongly be enhanced by bismuth incorporation.The physical properties of the films can be controlled by the chemical composition, the growth conditions and the crystallographic orientation. The sensor properties like sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The flexibility of ion substitution has led to promising applications of the magnetic garnet materials in microwave devices based on magnetostatic waves propagation [18], energy-independent information storage (bubble memory devices) [19,20], vertical Bloch line memory [21,22], a wide range of magneto-optic devices, i.e., shutters, modulators, deflectors, rotators [23][24][25][26][27]. As it can be seen from the above arguments, magnetic garnets still are among the most intensively studied magnetic dielectrics, and the last decade of the former century revealed many promising applications in sensors for epitaxial iron garnets having easy plane type magnetic anisotropy, for example, a magneto-optic visualization of the spatial distribution of magnetic field [28], for the non-destructive testing of high-temperature superconductors, eddy current imaging of defects in plated conducting materials, electric current topography in ICs, inductive and magneto-optical magnetic field sensors for different applications [29].…”
Section: Application Possibilities Of Different Types Of Garnetsmentioning
confidence: 99%
“…The flexibility of ion substitution has led to promising applications of the magnetic garnet materials in microwave devices based on magnetostatic waves propagation [18], energy-independent information storage (bubble memory devices) [19,20], vertical Bloch line memory [21,22], a wide range of magneto-optic devices, i.e., shutters, modulators, deflectors, rotators [23][24][25][26][27]. As it can be seen from the above arguments, magnetic garnets still are among the most intensively studied magnetic dielectrics, and the last decade of the former century revealed many promising applications in sensors for epitaxial iron garnets having easy plane type magnetic anisotropy, for example, a magneto-optic visualization of the spatial distribution of magnetic field [28], for the non-destructive testing of high-temperature superconductors, eddy current imaging of defects in plated conducting materials, electric current topography in ICs, inductive and magneto-optical magnetic field sensors for different applications [29].…”
Section: Application Possibilities Of Different Types Of Garnetsmentioning
confidence: 99%
“…It has been shown that the magneto-optical effects in magnetic iron-garnet films are very valuable in different applications of photonics, spintronics, sensorics, magnetometry, etc. [3][4][5]. In order to enhance the magneto-optical effect for these applications, various methods can be used.…”
Section: Introductionmentioning
confidence: 99%